Sensitive and Simple Method for the Spectrophotometric Determination of Paracetamol Drug Using Oxidative Coupling (International Journal of Psychosocial Rehabilitation, 2020)
Background: Paracetamol (N-acetyl-p-aminophenol) is famous as an analgesic and antipyretic drug. Paracetamol is utilized globally for antipyretic and analgesic activities. The spectrum of action is the same for NSAIDs and particularly resembles the COX-2 inhibitors. Be careful. Drug is, on typical, analgesic weak than N.S.AI.D.s or COX -2 inhibitors selective but is often desired because of its tolerance better. Thus, paracetamol has to be detached from the aqueous solution utilizing an effective way. However, study the object of the present to limit the effects of several conditions of the coupling oxidative colorimetric systems for the quantitative determinations of paracetamol. Methods: A highly simple and delicate optimal system via utilizing a spectrophotometric colorimetric way for the determination of paracetamol utilizing the coupling oxidative reaction of 4AAP in the basic medium in the presence of potassium ferricyanide to give a chromophore red color, which is spectrophotometrically limited at 510 nm at room temperature. Under the recommended ideal conditions, Beer’s law was obeyed in the range of 10-100 mg/L. Best linearity (r² = 0.9988). Results: The good concentration of reagent was gm/100 mland that of the potassium ferricyanide was gm/100 ml.